2019
DOI: 10.4300/jgme-d-19-00439
|View full text |Cite
|
Sign up to set email alerts
|

Medical Careers and Motherhood: A Cross-Sectional Study of Hispanic Female Physicians

Abstract: Background One factor many women consider when choosing a medical specialty is the plan to have children and the compatibility of their chosen specialty with motherhood. Objective We surveyed Hispanic female physicians who are mothers to collect demographic information, specialty choice, childbearing, and professional and personal life characteristics, along with respondents' suggestions for female physicians who want to start a family, and how hospitals and medical institutions could enhance their support of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The first was the effect of the responsibilities and preferences associated with pregnancy and parenthood on career motivation. Four studies found that motherhood did not reduce the motivation and ability of female doctors to return to work . A Dutch study found that female doctors who wanted or already had children remained motivated to work; a Swiss study found that 78 of 109 female doctors (72%) continued working more than half‐time after having children .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first was the effect of the responsibilities and preferences associated with pregnancy and parenthood on career motivation. Four studies found that motherhood did not reduce the motivation and ability of female doctors to return to work . A Dutch study found that female doctors who wanted or already had children remained motivated to work; a Swiss study found that 78 of 109 female doctors (72%) continued working more than half‐time after having children .…”
Section: Resultsmentioning
confidence: 99%
“…The second theme, derived from 17 quantitative studies (32 to 10 866 participants) 8,13,[19][20][21][22][23][24][25][26][27][28][29][30][32][33][34] and one qualitative study (eight participants), 31 was the impact of being a mother on working as a doctor (Supporting Information, table 3).…”
Section: Medicine: the Impact Of Being A Mother On A Medical Careermentioning
confidence: 99%
See 1 more Smart Citation
“…As some people might need help with tracking time, setting an alarm or using apps might be helpful. The combination of working from home and parenting has its own challenges, depending on the age of the child and the gender of the working parent [8][9][10]. Keep in mind that there are other activities in which you will have to invest your time, such as preparing food, taking care of children or cleaning.…”
Section: Be Organizedmentioning
confidence: 99%
“…As some people might need help with tracking time, setting an alarm or using apps might be helpful. The combination of working from home and parenting has their own challenges, depending on the stage of the child and the gender of the working parent (Lin & Burgard, 2018;Lopez-Leon, Del Valle, Salceda, Villegas-Pichardo, & Scosyrev, 2019;Ohu et al, 2019). Keep in mind that there are other activities in which you will have to invest your time, such as preparing food, taking care of children or cleaning.…”
Section: Tip 2 Be Organizedmentioning
confidence: 99%